The atypical presentation of rheumatoid arthritis in an elderly woman: a case report - Devaraj, Navin Kumar (College of Health Science of Jimma University, 2019)
The diagnosis of rheumatologic problem can be difficult, especially if not all the diagnostic criteria or typical clinical features are seen. This includes conditions such as rheumatoid arthritis which needs early diagnosis to start disease modifying drugs (DMARDs) which can improve the prognosis and prevent further joint erosion and organ damage. This case report focused on a similar scenario in an elderly woman initially thought to have osteoarthritis but was diagnosed later with rheumatoid arthritis which brought much relief to her current predicament.